Microcontroller-Driven Battery Management in Hybrid Energy Systems: A Systematic Review of Applications, Control Strategies, and Emerging Trends - Ripfumelo Humphrey Malele; Bongumsa Mendu; Bessie Baakanyang Monchusi (IEEE Access)
Microcontroller-driven battery management systems (BMS) are crucial for various applications, including electric vehicles, portable electronics, and renewable energy storage. These systems monitor and control critical parameters such as voltage, current, temperature, and state of charge to optimize battery performance and lifespan. Hence, this study aims to conduct a systematic literature review on microcontroller-driven battery management in hybrid energy systems by focusing on applications, control strategies, and emerging trends, among others. To collect documents, a systematic procedure was employed using targeted keywords to search within the Scopus database, while focusing on relevant, recent engineering papers. Eligible documents were refined, exported, and carefully assessed for relevancy, ensuring a comprehensive dataset for analysis. Among others, review findings highlighted that microcontroller-based systems are making big strides in renewable energy and battery management. Tools like Maximum Power Point Tracking (MPPT) and Pulse Width Modulation (PWM) help improve efficiency, while microcontrollers like Arduino and TMS320F28379D balance cost and performance depending on the project. Lithium-ion batteries are favored for their long life, but lead-acid batteries still have their place because they are cheaper. This study aims to contribute by conducting a systematic literature review using tailored keywords to identify and analyze advancements in microcontroller-driven battery management systems. Key contributions include reviewing innovations in battery charging systems, exploring hybrid systems integrating multiple power sources, examining control strategies and algorithms, and assessing renewable energy-based charging systems. The study further identifies patterns, themes, and emerging trends in the literature, highlights research gaps, and proposes directions for future work in this field.